2019
DOI: 10.25073/2588-1094/vnuees.4393
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indoor and Ambient Air Pollution at Complex Buildings in Hanoi

Abstract: The most typical air pollutants including PM10, CO, SO2, NOx are monitored at different sites indoor (basement, shopping malls) and outdoor (ambient air) of several complex buildings which are used for different purposes of resident, office, and shopping malls in Hanoi. The results show that the indoor air pollution concentrations tend to be higher than the corresponding pollutants of the ambient air. The results show the highest concentrations are in RC building for the same category of floor comparing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…While the effects of IAP on health have been studied extensively in many countries, especially in developed countries, but very limited in Vietnam. There are studies reported about the IAP level in complex building in urban area [16], kitchen room at rural area [17], and traffic mode (public bus) [18]. However, no published to present about air pollution level for indoor classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of IAP on health have been studied extensively in many countries, especially in developed countries, but very limited in Vietnam. There are studies reported about the IAP level in complex building in urban area [16], kitchen room at rural area [17], and traffic mode (public bus) [18]. However, no published to present about air pollution level for indoor classrooms.…”
Section: Introductionmentioning
confidence: 99%